La intervención educativa en la formación para el emprendimiento de los estudiantes del segundo y tercer año de bachillerato del Colegio Técnico Agropecuario “Salinas”, cantón Guaranda, provincia Bolívar, durante el año lectivo 2012 – 2013 - Quinatoa Pozo, Vinicio Germán (2013)
Today is consistently observed the urgent need to potentiate the development of knowledge , motivation and interests of Ecuadorean youth population through educational intervention which can significantly help define the progress of a project life really by matching internal potential of the individual and the environment , through a course called Entrepreneurship and Management within the parameters established by the academic curriculum that teaches the Ministry of Education, Universities like the country. As the content of the vision and mission of Salinas High School is projected form bachelors of great entrepreneurs like to continue their studies at the University for 28 years created ago, even today is strengthened exclusively with the subject of Entrepreneurship and Management for the second and third year of high school. Therefore the problem statement on the matter with their respective variables Independent and Dependent were operational zed in the formulation of the goals that allowed test the hypothesis , and consequently certain answers and results achieved to educational work , and commitment to entrepreneurship training is given . To this end we have made the assumption of different environments in the educational community that involves the emergence of a new social area where you have to know how to move and act. Hence the need to consider new educational challenges to capture the targets for change. In developing the theoretical framework , we recorded in the first instance the scientific theory of Educational Intervention initial foundation of our work where learning and success of students prior to a process of psycho- cognitive affective character and motor is not disputed that is treated in time but a permanent attitude and confidence for their effective development in strategic training new entrepreneurs elements active , aware and responsible XIII for new alternatives of their propositions , all these topics and subtopics current is described in the scientific theory taking into account two variables. Properly reinforced in the research work by the conceptual, reference , legal and situational theory. In its development is considered the approaches to acquire sustenance work properly grounded through methods , techniques, tools and investigative processes to determine the plan processing and statistical analysis of results as required under Regulation Research and Development Theses As to the methods and techniques were applied the most appropriate responsiveness to meeting the objectives proposed by the surveys made to teachers and students , as reflected in the tabulation of data and interpreted in the representation of statistical tables , graphs allow to formulate conclusions and recommendations. The proposal appears mainly to get a change of behavior in the future high school students who purchase a College Salinas entrepreneur training quality through educational influence , where prevails the identification of interfaces of learning for empowerment and development of this discipline through work restructuring on teachers in their methodologies, in linking to the salt company and tracking changes to the processing elements . Linking the school with the community enterprise , strengthening teamwork , conducting internships Strategies for change in research to strengthen the creation of innovative knowledge through the training of managers and teachers exists courtiers -level processes , the graduates to follow through a plan of results , the application in the teaching of the principles of respect and affection , inducing a credit culture , creating opportunities to loan the use of resources context , the creation of a policy evaluation and measurement of achievements , compliance with the institutional mission and vision , and prevail technological and commercial development of the XIV students. The main results obtained in the investigation it is determined that students got major initiatives and leadership in group work. Teachers provide a quality educational service with warmth consistent with the formation of the new Ecuadorian citizen. The Directors and teachers of the institution establish compliance of agreements linking with local businesses in achieving student practices, meetings with parents are participatory in planning and coordinating activities, plus support for the implementation of both internal and external internships of their clients.